Fuzzy logic model for the prediction of bond strength of high-strength lightweight concrete - Tanyildizi, Harun (Elsevier Sci Ltd, 2009)
In this study, a fuzzy logic prediction model for the bond strength of lightweight concrete containing mineral admixtures under different curing conditions was devised. A control concrete mixture containing only Portland cement, another mixture having fly ash replacing 15% by mass of cement, and a third mixture having silica fume replacing 10% by mass of cement are produced, and all specimens from these three mixtures are cured in three different conditions, which are: (1) in water tank of 20 +/- 2 degrees C, (2) sealed in plastic bags in the laboratory, and (3) in air in the laboratory. At the end of each curing period, three specimens out of each concrete combination and curing condition were tested for compressive and bond strengths, and the average of three values were taken. The results obtained from the fuzzy logic prediction model were compared with the average results of the experiments, and they were found to be remarkably close to each other. The results show that the fuzzy logic can be used to predict bond strength of lightweight concrete. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bond strength; Lightweight concrete; Curing conditions; Fuzzy logic